Discrete choice cannot generate demand that is additively separable in own price - Jaffe, Sonia; Kominers, Scott Duke (Economics Letters, 2012)
We show that in a unit demand discrete choice framework with at least three goods, demand cannot be additively separable in own price. This result sharpens the analogous result of Jaffe and Weyl (2010) in the case of linear demand and has implications for testing of the discrete choice assumption, out-of-sample prediction, and welfare analysis.